Acute Kidney Injury Epidemiology in pediatrics - Cleto-Yamane,Thais Lira (2019)
Abstract We performed a search in the MEDLINE database using the MeSH term: "Acute Kidney Injury", selecting the subtopic "Epidemiology", and applying age and year of publication filters. We also searched for the terms: "acute renal failure" and "epidemiology" "acute tubular necrosis" and "epidemiology" in the title and summary fields with the same filters. In a second search, we searched in the LILACS database, with the terms: "acute renal injury", or "acute renal failure" or "acute kidney injury" and the age filter. All abstracts were evaluated by the authors and the articles considered most relevant, were examined in their entirety. Acute Kidney Injury (AKI) -related mortality ranged from 3-63% in the studies included in this review. AKI etiology has marked regional differences, with sepsis being the main cause in developed countries. In developing countries, primary renal diseases and hypovolemia are still a common cause of AKI.